Acute presentation of cocoon abdomen as septic peritonitis mimicking with strangulated internal herniation: a case report - Sabah Uddin Saqib; Rimsha Farooq; Omair Saleem; Sarosh Moeen; Tabish Umer Chawla (Surgical Case Reports)
Abstract Background Abdominal cocoon syndrome is a rare cause of intestinal obstruction in which loops of small bowel get entrapped inside a fibro-collagenous membrane. Condition is also known in the literature as sclerosing peritonitis and in the majority of cases, it has no known cause. Although the majority of patients exhibit long-standing signs and symptoms of partial bowel obstruction in an out-patient clinic, its acute presentation in the emergency room with features of sepsis is extremely rare. This case report aims to describe the emergency presentation of cocoon abdomen with septic peritonitis. Case presentation A 35-year-old male with no known co-morbidity and no prior history of prior laparotomy presented in emergency room first time with a 1-day history of generalized abdomen pain, vomiting, and absolute constipation. He was in grade III shock and had metabolic acidosis. The clinical impression was of the perforated appendix, but initial contrast-enhanced computed tomography (CECT) was suggestive of strangulated internal herniation of small bowel. Emergency laparotomy after resuscitation revealed hypoperfused, but viable loops of small bowel entrapped in the sclerosing membrane. Extensive adhesiolysis and removal of the membrane were performed and the entire bowel was straightened. Postoperatively he remained well and discharged as planned. Histopathology report confirms features of sclerosing peritonitis. Discussion Cocoon abdomen is a very rare cause of acute small bowel obstruction presenting in an emergency with features of septic peritonitis. Condition is mostly chronic and generally mimics abdominal TB in endemic areas like India and Pakistan. A high index of suspicion is required in an emergency setting and exploratory laparotomy is diagnostic and therapeutic as well and the condition mimics internal herniation in acute cases. Conclusion Cocoon abdomen as a cause of septic peritonitis is extremely rare and might be an unexpected finding at laparotomy. Removal of membrane and estimation of the viability of entrapped bowel loops is the treatment of choice, which may require resection in the extreme case of gangrene.